The Impact of Chinese Investment on Skill Development and Technology Transfer in Zambia and Malawi's Cotton Sector - Tang Xiaoyang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2019)
This paper by Tang Xiaoyang looks into China-Africa Cotton (CAC), one of the first Chinese cotton firms to enter the African market. The study analyzes China-Africa Cotton's operations in Zambia to investigate the impact on the technological development of the local cotton sector. As a new player in the arena, CAC has business models and a management style that differ from those of previous foreign investors in the region. Within six years, CAC has grown from a sole ginnery into a firm with tens of thousands of contracted outgrowers, and is now a comprehensive multinational business with an integrated value chain.
Keywords: 330